Be part of something special: Specialist Groups in the IWA - Zainudin, Zaki (Young Water Professionals, IWA, 2013)

(untitled)
There are various Specialist Groups (SGs, sometimes referred to as “interests groups”) in the IWA where members can share and contribute ideas pertaining to particular of interest in the water field. A management committee typically oversees the running and activities of these groups. There are various benefits of joining the SGs, especially if you are lucky enough to be part of the management committee. This article describes my thoughts and views on the matter, being part of the Watershed and River Basin Management SG.